P102 Subclinical atherosclerosis assessed by coronary artery calcium score in patients with Crohn's disease. (25th January 2019) - Rocha, B; Nomura, C; Rocha, M; Lopes, B; Azevedo, M; Carlos, A; Carrillo, F; Damiao, A; Sipahi, A; Leite, A
Abstract: Background: Several immune-mediated diseases such as rheumatoid arthritis, systemic lupus erythematosus and psoriasis are associated with an increased risk of cardiovascular disease (CVD). 1 However, there are conflicting data as to whether inflammatory bowel diseases (IBD) increase risk for CVD. 2 We aimed to evaluate coronary artery calcium (CAC) score as an accurate predictor of cardiovascular event in patients with Crohn's disease. Methods: We investigated 150 patients with Crohn's disease (mean age, 43.4 ± 5.9 years) and 75 age- and sex-matched controls (mean age, 43.6 ± 5.6 years) without prior known CVD and traditional risk factors for atherosclerosis such as hypertension, dyslipidemia, diabetes, smoking, obesity, and family history of coronary disease. All participants underwent a computed tomography for the measurement of CAC and the calcification extent was measured by means of the Agatston score. CAC was considered a qualitative variable (CAC = 0 and CAC > 0). Results: The two groups were similar in respect to age, sex and Framingham risk score. Nevertheless, there were differences in body mass index, systolic blood pressure and lipid profile, even though all these parameters were within normal range in both groups. Serum C reactive protein and albumin differed between groups. Among patients with Crohn, disease activity scores, years since diagnosis and the use of immunomodulators and/or biologic therapy were similar in those with and without coronary artery calcification. Those with calcification were older ( p = 0.022) and more likely to be male ( p = 0.058). Conclusions: The current findings show that patients with Crohn's disease without traditional cardiovascular risk factors do not exhibit higher coronary artery calcification. Cardiovascular risk is still a conflicting issue in IBD and further studies are needed to clarify the relationship between CVD and IBD. References 1. Staniak HL, Bittencourt MS, de Souza Santos I, et al . Association between psoriasis and coronary calcium score. Atherosclerosis 2014;237:847–52. 2. Osterman MT, Yang Y-X, Brensinger C, et al. No increased risk of myocardial infarction among patients with ulcerative colitis or Crohn's disease. Clin Gastroenterol Hepatol 2011;9:875–80.